VITAMIN D DEFICIENCIES: A PILOT STUDY IN OVERWEIGHT AND OBESE CHILDREN AND ADOLESCENTS - Rosli, Nur Faten Hafizah; Nor, Noor Shafina Mohd; Adnan, Rose Adzrianee; Kadir, Siti Hamimah Sheikh Abdul (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION In the post COVID era, the prevalence of overweight and obesity in children and adolescents is increasing, leading to multiple obesity-related comorbidities. Despite Malaysia being a tropical country, the occurrence of vitamin D deficiency has been increasing. This study aimed to determine the incidence of vitamin D deficiencies in normal and obese/overweight groups. METHODOLOGY A total of 43 participants aged 7 to 17 years old were recruited from the Hospital Al-Sultan Abdullah, UiTM. During the hospital visit, anthropometric measurements and a questionnaire on dietary intake, sunlight exposure and average family income were collected. Total serum vitamin D levels were taken and analysed using the electrochemiluminescence assay. RESULT The mean age of the participants was 9.30 ± 1.89 years old. A total of 48.8% were overweight or obese. The overweight/ obese group had a significantly higher body mass index (BMI) (29.01 ± 11.23 kg/m2 vs 14.95 ± 1.77 kg/m2 , p <0.01), weight (54.73 ± 22.7 kg vs 24.23 ± 7.24 kg, p <0.01) and waist circumference (82.65 ± 23.27 cm vs 55.66 ± 5.10 cm, p <0.01) compared to the normal group. Male participants had significantly higher BMI (23.8 ± 8.27 kg/m2 vs 19.92 ± 12.31 kg/m2 , p <0.05) and weight (47.14 ± 25.71 kg vs 31.47 ± 16.23 kg, p <0.05 compared to female. A total of 60.5% of the participants had serum 25 (OH) D levels ≤50 nmol/L. There were no significant differences in 25 (OH) D levels between both groups. Additionally, daily exposure to sunlight for more than 2 hours was associated with higher serum vitamin D levels among children and adolescents (p <0.05). Furthermore, a high household income was associated with a high risk of weight gain (p <0.01) and waist circumference (p <0.01) among children and adolescents. CONCLUSION There was a high incidence of vitamin D deficiencies in children and adolescents with no association between BMI and serum 25 (OH) D levels.